Sequential modulations of the Simon effect depend on episodic retrieval - Spapé, Michiel M.; Hommel, Bernhard (Frontiers in Psychology, 2014)
Sequential modulations of conflict effects, like the reduction of the Simon effect after incompatible trials, have been taken to reflect the operation of a proactive control mechanism commonly called conflict monitoring. However, such modulations are often contaminated by episodic effects like priming and stimulus-response feature integration. It has previously been observed that if the episodic representation of a conflicting trial is altered by rotating the stimulus framing 180 degrees around its axis, the subsequent “conflict adaptation” pattern is eliminated. In Experiment 1, we replicate the findings and provide the basic episodic interpretation. In Experiment 2, we extend the framework to include rotations of 90 degrees, and verify that the episodic effects generalise to scenarios of neutral compatibility. Finally, in Experiment 3, we add complete, 360-degree rotations, and show that the episodic manipulation by itself does not eliminate the conflict adaptation patterns – as long as conditions favour episodic retrieval. The experiments are argued to demonstrate that an episodic account of the conflict adaptation effect can most parsimoniously account for the behavioural effects without relying on higher order cognition. Accordingly, we conclude that conflict adaptation can be understood either as critically depending on episodic retrieval, or alternatively reflecting only episodic retrieval itself.